ALAT PENILAIAN PEMBELAJARAN: IMPLEMENTASI ALAT ANALISIS UNTUK TUJUAN BELAJAR - Upiyani, Upiyani; Cahyawati, Ita Cahyawati; Supendi, Sinta Silvia Supendi; Bachtiar, Mahdum Bachtiar; Hunainah , Hunainah Hunainah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2023)
The purpose of this research is to explore the learning evaluation tool. The research methodology used in this study adopts a model approach, specifically using Content Analysis. The main source of data that has been analyzed is the content contained in the learning evaluation tool. Evaluation is a systematic procedure that involves the collection of diverse data to provide a comprehensive assessment of student progress in learning. It is important for teachers to have a comprehensive understanding of student development to effectively ensure the successful completion of the learning process. In a broad sense, evaluation instruments can be categorized into two different types: non-test and test-based. Often, both categories of evaluation tools are referred to as evaluation methodologies. The classification of test techniques or methods for test performance can be categorized in three different ways, namely: 1) Examination in written form, 2) Oral testing and 3) Practical testing. In order to ensure reliable evaluation, it is essential that the evaluation tool has a high quality standard, along with other influential elements such as the performance of the test itself, the competence of the examiner responsible for managing and verifying the test results, and the environmental conditions in which evaluation is carried out.